Bianco Assoluto/White. - Marcone, Gaspare Luigi (Brescia, KANALIDARTE., 2012)
Bonalumi, Agostino ; Castellani, Enrico ; Dadamaino ; Fontana, Lucio; Goepfert, Hermann ; Leblanc, Walter ; Manzoni, Piero ; Megert, Christian ; Peeters, Henk ; Simeti, Turi ; Spindel, Ferinand ; Uecker, Günther ; Von Graevenitz, Gerhard
Catalogus bestaat uit 2 delen (kunstwerken en tekst)
Bianco Assoluto/White, Kanalidarte, Brescia, november 17 - december 21, 2012, Bianco Assoluto/White, MDZ art gallery, Knokke, December 29 - January 29, 2013
boek